2019
DOI: 10.1111/are.14295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary lipid levels on growth, fatty acid composition, antioxidant status and lipid metabolism in juvenileOnychostoma macrolepis

Abstract: Five diets of different lipid levels, 3%, 6%, 9%, 12% and 15% (L3, L6, L9, L12 and L15), were designed and fed to juvenile Onychostoma macrolepis for 8 weeks. The juvenile O. macrolepis grew better at L9 than at L3, L6 and L15 (p < .05). The viscera and hepatopancreas indexes increased as the dietary lipid levels increased. There appeared lower serum TG and HDL levels at lipid levels of 3.01%–9.01% (p < .05). Hepatic histology showed that the fish fed on L15 diet had more hepatic lipid droplets than those fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 55 publications
4
12
1
Order By: Relevance
“…HDL-c can absorb free cholesterol in extrahepatic tissues (Zhang et al, 2013). An earlier study reported that TC and TG contents significantly increased when the dietary lipid content increased (Gou et al, 2019;Wang et al, 2016;Zhao et al, 2016), which was contradictory to our findings where the contents of TC and TG in NEFA levels were closely related to various diseases such as obesity, insulin resistance and pancreatic D cell dysfunction (Boden & Shulman, 2002). In this study, the significantly higher NEFA content of fish in D4 and D5 group indicated a higher risk of disease than that in other groups.…”
Section: Analysis Of the Differences In Intestinal Microbiotacontrasting
confidence: 99%
“…HDL-c can absorb free cholesterol in extrahepatic tissues (Zhang et al, 2013). An earlier study reported that TC and TG contents significantly increased when the dietary lipid content increased (Gou et al, 2019;Wang et al, 2016;Zhao et al, 2016), which was contradictory to our findings where the contents of TC and TG in NEFA levels were closely related to various diseases such as obesity, insulin resistance and pancreatic D cell dysfunction (Boden & Shulman, 2002). In this study, the significantly higher NEFA content of fish in D4 and D5 group indicated a higher risk of disease than that in other groups.…”
Section: Analysis Of the Differences In Intestinal Microbiotacontrasting
confidence: 99%
“…The present study found that the fish fed with 169. baerii were improved very obviously, indicating that within a reasonable range, increasing the lipid level in the diet could promote the growth, consistent with results obtained in previous studies (Guo et al, 2019;Meng et al, 2019;Wang et al, 2018). It was reported in a variety of fish species that dietary lipid level 40-50 g/kg higher than the optimal dose induced decline of growth (Chang et al, 2018;Gou et al, 2019;Han et al, 2014;Kikuchi et al, 2009). However, in our current study, the growth of Acipenser baerii kept stable from L17 (169.3 g/kg) to L25 (248.8 g/kg), suggesting Acipenser baerii might have a better tolerance to high-lipid diets.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, if faced with an excess of dietary lipid supplement, upregulation in the expression levels of FAS, ACC-1, and SREBP1 and relative downregulation in the expression levels of LPL and CPT1 in the hepatopancreas of large-sized common carp were conducted to maintain the dynamic and metabolic balance between the absorption and utilization of exogenous dietary lipids and endogenous lipid synthesis (51). Similar findings were reported in rainbow trout (52), GIFT tilapia (Oreochromis niloticus) (53), and Onychostoma macrolepis (54). In addition, it needs to be emphasized that the lowest expressions of lipogenic genes and lipolysis genes in the hepatopancreas were observed in the 30 g/kg treatment, indicating that a restrictive and an insufficient lipid intake induced to nutritional dysregulation stress for large-sized common carp (55).…”
Section: Discussionsupporting
confidence: 53%